Association between systemic immune-inflammation index at admission and post-stroke depression in patients with acute ischemic stroke - Su, Xiaohang; Chi, Fengtian; You, Jiulin; Zhao, Jueyu; Wang, Sanqi; Zhou, Xinyu; Li, Xin (Frontiers in Neurology, 2025)
BackgroundPost-stroke depression (PSD) is one of the most common neuropsychiatric complications among stroke survivors, with a substantial impact on functional recovery and quality of life. This study aimed to investigate the association between the systemic immune-inflammation index (SII) at admission and the occurrence of PSD in patients with acute ischemic stroke (AIS).MethodsWe prospectively enrolled 318 consecutive patients with first-ever AIS admitted to our hospital between August 2024 and March 2025. Venous blood samples were collected at admission, and SII was calculated as neutrophil count × platelet count/lymphocyte count. At 3 months post-stroke, depressive symptoms were assessed using the 17-item Hamilton Depression Rating Scale (HAMD-17). Patients with a HAMD-17 score >7 were diagnosed with PSD and categorized accordingly into PSD and non-PSD groups.ResultsAt the 3-month follow-up, 98 patients (30.82%) were diagnosed with PSD. Compared with the non-PSD group, patients in the PSD group had significantly higher SII values [658.66 (468.73–958.90) vs. 476.71 (362.73–646.83), p < 0.001]. In multivariate logistic regression analysis, after adjusting for potential confounders, patients in the highest SII tertile had a significantly increased risk of developing PSD compared with those in the lowest tertile (OR = 3.502, 95% CI: 1.582–7.752, p = 0.002). Receiver operating characteristic (ROC) curve analysis identified an optimal SII cut-off value of 602.503 for predicting PSD, with a sensitivity of 0.582, a specificity of 0.700, and an area under the curve (AUC) of 0.659 (95% CI: 0.592–0.726, p < 0.001).ConclusionElevated SII levels at admission are positively associated with the development of PSD in AIS patients, suggesting that SII may serve as a valuable inflammatory biomarker for early identification of patients at high risk for PSD.